A life-cycle approach to environmental, mechanical, and durability properties of "green" concrete mixes with rice husk ash. (20th January 2016) - Gursel, Aysegul Petek; Maryman, Helena; Ostertag, Claudia
Abstract: Among the possible solutions to a sustainable future is to limit the consumption of non-renewable resources and to minimize waste and its associated releases. Using supplementary cementitious materials (SCMs) in concrete constitutes environmental, societal and economic benefits towards the sustainability goal. Similar to the commonly used fly ash, rice husk ash (RHA) is a highly-reactive pozzolanic material, and can replace up to 30% of portland cement in concrete mix designs. In the United States, concrete with RHA is still a niche product. In recent years, fly ash supply has declined due to decreasing coal use, general economic stagnation, and regulatory uncertainties despite the increase in its utilization in concrete products. However, RHA has the potential to meet the demand from decreasing fly ash supplies. The focus of this study is to analyze the performance of ternary- and quaternary-RHA blend concrete mixes in terms of their durability, mechanical properties, and global warming potential (GWP) and criteria air pollutants. A life-cycle assessment (LCA) approach has been conducted for the quantification of environmental impacts. Results have shown that ternary and quaternary concrete mixes with RHA and fly ash resulted in lower GWP while improving the durability of mixes without compromising design strength. Highlights: GWP per unit volume of concrete mixture decreases with decreasing amount of portland cement per unit volume of mixture. Portland cement production and transportation are significant sources of GWP and criteria air pollutants. For a given strength, lower CO2 -eq intensities are achieved by replacing cement with RHA and fly ash. SCMs in concrete results in lower GWP and criteria air pollutants while improving durability of structures.